2012
DOI: 10.1111/j.1468-0106.2012.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Finance by Small and Medium Enterprises: a Cross‐Country Analysis with A New Data Set

Abstract: Access to finance has always been a challenge for small and medium enterprises (SMEs), but the need to address this issue became more pronounced after the global financial crisis, as SMEs are perceived as engines of growth and job creation. However, lack of consistent indicators for SME finance at the country level restricts cross‐country analyses. The present paper introduces a supply‐side data set to fill this gap, and provides the first set of analyses with this new data set. Global SME lending volume is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…Our results present affirmative results with the works of other authors. Ardic, Mylenko, and Saltana (2012) state that the problem of obtaining of the bank loans by the SMEs has further increased during the economic crisis, when SME financing was significantly reduced in the developed countries. Economic & Social Research Council (2010) states that overdraft loan rejections increased 3½ times (from 4.2% to 15.3%), term loan rejections increased 2½ times (from 6.1% to 16.3%), overdraft margins increased by 83% (from 2.4% points to 4.4% points over base), overdraft arrangement fees increased by 86% (from £237 to £442), term loan margins increased by 68% (from 2.2% to 3.7% points over base), term loan arrangement fees increased by 37% (from £1,074 to £1,468) in the United Kingdom in 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Our results present affirmative results with the works of other authors. Ardic, Mylenko, and Saltana (2012) state that the problem of obtaining of the bank loans by the SMEs has further increased during the economic crisis, when SME financing was significantly reduced in the developed countries. Economic & Social Research Council (2010) states that overdraft loan rejections increased 3½ times (from 4.2% to 15.3%), term loan rejections increased 2½ times (from 6.1% to 16.3%), overdraft margins increased by 83% (from 2.4% points to 4.4% points over base), overdraft arrangement fees increased by 86% (from £237 to £442), term loan margins increased by 68% (from 2.2% to 3.7% points over base), term loan arrangement fees increased by 37% (from £1,074 to £1,468) in the United Kingdom in 2008.…”
Section: Resultsmentioning
confidence: 99%
“…The assumption that an access to finance is necessary for growth and further development of SMEs was also proven by such authors as Mercieca, Schaeck and Wolfe (2009). Ardic, Mylenko and Saltane (2012), researchers at the World Bank, reported on SMEs access to finance in the form of a cross-country analysis and they agreed that access to finance of SMEs is strongly correlated to their growth. Mueller and Zimmermann (2009) state that the lack of the access to finance is a great constraint especially for smaller companies.…”
Section: Difficulties In Financing Of Smes -Literature Reviewmentioning
confidence: 85%
“…Some of such initiatives may be adoption of sophisticated technology like spreading out producing processes, utilizing innovative means, enhancement of quality in processes, utilizing micro-irrigation mechanism and maintaining schedules of plantation and record of such schedule, quantum of plantation and expected productivity and likely date of harvesting. Ardic, et al [61] analyzed the global flow of credit to SME sector and found that a total of 10 trillion $ credit is extended to SME sector in the world and OECD nations account for 70% of such credit. The study has revealed that credit to SMEs work out to 3% and 13% of GDP of developing and developed nations respectively.…”
Section: Structure Of Supply Chain Segmentsmentioning
confidence: 99%